Development of East Baghdad Oil Field By Clusters of Horizontal Wells - A.Alrazzaq, Ayad A.Alhaleem (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
There are varieties of reasons lead for drilling horizontal wells rather than verticals. Increasing the recovery of oil, especially from thin or tight reservoir permeability is the most important parameter. East Baghdad oil field considered as a giant field with approximately more than 1billion barrel of a proved reserves accompanying recently to low production rate problems in many of the existing wells. It is important to say that presence of of horizontal wells in East Baghdad field especially by converting some of already drilled wells by re-entry drilling horizontal sections may provide one of best solutions for the primary development stage in East Baghdad field which may be followed by drilling new horizontal wells or using multilateral wells. Advance software (Well Test/FAST) has been used to convert the production data for the already drilled vertical wells to horizontals to simulate the productivity. It can be concluded that no measurements available for the ratio of anisotropy (Kv/Kh); in East Baghdad Oil Field therefore, the wells productivity has been estimated using wide range of anisotropy ratios that will help the field operator to determine exactly wells productivity. Moreover, it helps to recommend the effectiveness of applying hydraulic fracturing in improving horizontal well productivity. The results show that it could be used well EB-32 as a re-entry horizontal well with an optimum section length of 1500-2000ft wich give the best production rate. The same result could be stated for EB-10 with somewhat higher productivity than EB-32.